Raton Telephone Directory, November 1952. - frey50 (Raton, NM Coda Publications, 2006)
First published by Mountain States Telephone & Telegraph Company, This reproduction of the 1952 Raton phone directory was done by William Carroll in 2006. A fascinating picture of the city at the time.
Includes bibliographical references (p. 23) and index.
83560
Keywords: Raton, NM--telephone directories; Mountain States Telephone & Telegraph Company--telephone directory; Office Copy